Satisfaction of the Patients cared for in the Dental Clinic of the Cooperative University of Colombia (Revista Nacional de Odontología, 2016)
Introduction: The patients’ satisfaction of the health services received is a key element in the measurement of the quality of the attention. Objective: To describe the patient’s satisfaction that received care at the adult clinic of the Dental School of the Cooperative University of Colombia, in the facility of Medellin and Envigado, Colombia. Materials and Methods: Cross-sectional descriptive study. A representative sample was estimated from 188 patients that were randomly surveyed, given previous informed consent. A descriptive analysis was performed.Results: 68.1% were women with an average age of 34.04 ± 9.71 years. 68% requested consultation for fixed prosthesis, 16, and 5% for removable dentures, 14.4% for total prostheses and 1.1% for teeth whitening. 100% of the population served informs they received good treatment from the student, professor and the clinic staff. All the patients consider their reason for consultation was solved. 95, 7% of the patients would consult at that clinic again and 99% would recommend the dental services. The patient’s perception regarding the physical installations was generally high for hygiene and illumination (97%), the order (96%) and ventilation (83%). Privacy was the only factor assessed poorly (3.2%).Conclusions: The patients treated at the integral adult clinic were satisfied with the attention received and their reason for consultation was resolved. The patients mainly requested consultation for the treatment of fixed or partially removable prosthesis. Most of them agreed to return and recommend the clinic’s service to third parties, and have an excellent opinion regarding interpersonal relationships, and a good opinion regarding the physical installations, except for the patient’s privacy.
Keywords: quality of health services; dental students; dental school; clinical practices; satisfaction